2006
DOI: 10.1128/aac.50.5.1753-1761.2006
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals Mechanisms by Which Lactococcus lactis Acquires Nisin Resistance

Abstract: Nisin, a posttranslationally modified antimicrobial peptide produced by Lactococcus lactis, is widely used as a food preservative. Yet, the mechanisms leading to the development of nisin resistance in bacteria are poorly understood. We used whole-genome DNA microarrays of L. lactis IL1403 to identify the factors underlying acquired nisin resistance mechanisms. The transcriptomes of L. lactis IL1403 and L. lactis IL1403 Nis r , which reached a 75-fold higher nisin resistance level, were compared. Differential e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 59 publications
(60 reference statements)
5
109
0
Order By: Relevance
“…In Group A streptococcus, a TCS was shown to be induced by human saliva, which could also cause cell wall damage because it is rich in lysozyme (49). A link between spxB and the cell wall stress response is supported by recent transcriptome results on L. lactis strain IL1403 that had acquired resistance to the cell wall-targeted antimicrobial peptide nisin: in this strain, spxB (yneH), oatA (yvhB), and cesSR (kinD llrD) were among the up-regulated genes (50).…”
Section: Discussionmentioning
confidence: 59%
“…In Group A streptococcus, a TCS was shown to be induced by human saliva, which could also cause cell wall damage because it is rich in lysozyme (49). A link between spxB and the cell wall stress response is supported by recent transcriptome results on L. lactis strain IL1403 that had acquired resistance to the cell wall-targeted antimicrobial peptide nisin: in this strain, spxB (yneH), oatA (yvhB), and cesSR (kinD llrD) were among the up-regulated genes (50).…”
Section: Discussionmentioning
confidence: 59%
“…Additionally, this study showed that wild-type strains of Staphylococcus bearing additional copies of the dlt operon contained larger amounts of Dalanylated teichoic acids and hence repelled cationic proteins more effectively and were less sensitive to gallidermin (45). It was also notable that spontaneously nisin-resistant mutants of L. lactis IL1403 expressed the dlt and gal operons at higher levels (51). The relevance of the gal operon, associated with the Leloir pathway (52), is that galE encodes a UDP-glucose 4-epimerase that is responsible for the synthesis of ␣-galactose, which is transported across the membrane to become a substituent of LTA.…”
Section: Dltamentioning
confidence: 78%
“…This observation led to further studies of L. lactis MG1363, which established that L. lactis MG1363 ⌬galAMK was twice as sensitive to nisin as the wild type, suggesting that ␣-galactose incorporation has an effect on LTA structure and thus is important in nisin resistance. In addition, the LTA of the resistant strain contained twice as much ␣-galactose as the wild type, which may indicate a more densely packed LTA, ultimately making the cell wall barrier less negatively charged due to the action of DltA (51). Nisin-resistant cells also appeared to have more lipoteichoic acid than nisin-sensitive cells.…”
Section: Dltamentioning
confidence: 90%
See 1 more Smart Citation
“…lactis ⌬cesR mutant was two times more sensitive to nisin, although this peptide did not activate the cesFSR promoter (441). Nevertheless, a nisin-resistant strain obtained through a nisin adaptation process overexpressed cesFSR and its regulon (383). The cesFSR system is also induced by vancomycin, bacitracin, and the bacteriocins plantaricin C and Lcn972 (441).…”
Section: Mechanosensitive Channelsmentioning
confidence: 97%